2020
DOI: 10.1007/s00259-020-04864-1
|View full text |Cite
|
Sign up to set email alerts
|

A CT-based radiomics model to detect prostate cancer lymph node metastases in PSMA radioguided surgery patients

Abstract: Purpose In recurrent prostate carcinoma, determination of the site of recurrence is crucial to guide personalized therapy. In contrast to prostate-specific membrane antigen (PSMA)–positron emission tomography (PET) imaging, computed tomography (CT) has only limited capacity to detect lymph node metastases (LNM). We sought to develop a CT-based radiomic model to predict LNM status using a PSMA radioguided surgery (RGS) cohort with histological confirmation of all suspected lymph nodes (LNs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 46 publications
(53 reference statements)
1
42
0
Order By: Relevance
“…Segal et al [ 13 ] demonstrated that features in radiological images can be used to reconstruct the majority of the tumor genetic profile. Radiomics data successfully predicted overall survival [ 14 , 15 ], metastases development [ 16 , 17 ] or histological properties [ 18 , 19 ] and may be used as a decision support system in clinical practice. Radiomics approaches to determine the HPV status achieved areas under the receiver operating characteristic curve (AUC) of about 70% to 80%, when tested on external data sets [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Segal et al [ 13 ] demonstrated that features in radiological images can be used to reconstruct the majority of the tumor genetic profile. Radiomics data successfully predicted overall survival [ 14 , 15 ], metastases development [ 16 , 17 ] or histological properties [ 18 , 19 ] and may be used as a decision support system in clinical practice. Radiomics approaches to determine the HPV status achieved areas under the receiver operating characteristic curve (AUC) of about 70% to 80%, when tested on external data sets [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The RSF was developed with 1000 trees. Hyperparameter optimization was conducted for node size (search space [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and the number of input variables randomly chosen at each node (mtry) (search space 2-10). For ENR, alpha (search space 0.05-1.0) and lambda were optimized.…”
Section: Modeling Strategymentioning
confidence: 99%
“…It is defined as an algorithm-based large-scale quantitative analysis of imaging features [ 12 , 13 , 14 , 15 ]. Such imaging biomarkers were shown to predict survival, tumor progression, spatial infiltration, and molecular aberrations in a multitude of cancer types [ 16 , 17 , 18 , 19 , 20 , 21 ]. In a recent publication, Spraker et al did demonstrate a prognostic potential of contrast-enhanced and fat-saturated T1-weighted (T1FSGd) sequence-based radiomics in STS patients [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Delineation of ROI is conducted manually, semi-automatically or fully automatically. Manual segmentation requires experienced radiologists to contour the full tumor regions, which is still regarded as the gold standard in many applications [ 25 , 26 , 27 ]. Semi-automatic segmentation is usually realized by thresholding and region-growing techniques, which is more efficient as it requires less manual intervention [ 28 , 29 ].…”
Section: Machine Learning and Radiomics Workflow For Oncology Imagingmentioning
confidence: 99%